Framtidsförväntningar och fiendebilder. Samtida muslimsk och kristen apokalyptik - Jakob Wirén (Svensk Teologisk Kvartalskrift, 2013)
The purpose of this article is to analyze and compare some of the popular, and yet marginalized apocalyptic narratives in contemporary Muslim and Christian thought. Obviously, the two traditions have many things in common and yet there is an apparent antagonism between them. In order to further investigate into the tensions between Muslim and Christian apocalypticism, this article will focus on how ‘the Others’ are portrayed in these narratives: who are ‘they’ and what is their place in the apocalyptic schemes?